Factors affecting contractor’s bidding success for international infrastructure projects in australia - Aznar, Beltrán; Pellicer, Eugenio; Davis, Steven; Ballesteros-Pérez, Pablo (Journal of Civil Engineering and Management, 2017)
This paper examines the effects of different factors on the success or failure of bids for infrastructure projects in Australia. Logistic regression analysis was used to empirically determine which factors have the largest effect on bidding success. Data was collected from 123 bids submitted by several infrastructure companies with subsidiaries in Australia. The analysis found that having a competitive advantage and a local partner, and also not competing against a local company were the most important factors; as they significantly increase the chances of success. However, four other factors, having relevant expertise, resource availability, a previous relationship with the client, and a previous relationship with consortium members, are ‘essential’ to be able to compete; as the absence of any of these four factors results in bid failure, although having them is not a guarantee of success. Results of this paper provide valuable information for any company considering the opportunity of entering into Australia’s infrastructure market as well as for companies that are already present in that country and are considering whether to bid for a specific project.